1998
DOI: 10.1007/bf03395292
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Computer-Interactive Self-Assessment with and Without Feedback

Abstract: Following a preexperimental assessment of computer-interactive math performance during VR 6 reinforcement and extinction, 4 regular education students and 2 students identified as behaviorally disordered participated in an A-BC-D-BC withdrawal of treatment design. Subsequent to baseline observations of math performance during self-assessment with and without accuracy feedback, students were trained in self-assessment procedures by way of a series of computer-interactive tutorials. During treatment, students we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…This resulted in a final sample of nine journal articles, describing 14 experimental studies. However, after reading these papers, both reviewers discarded five studies (i.e., Gaschler, Marewski, Wenke, & Frensch, 2014; Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986; McAuliffe, Hughes, & Barnes-Holmes, 2014, Experiment 1; Ninness, Ninness, Sherman, & Schotta, 1998) because they did not state in the abstract or introduction that their aim was to investigate pliance, tracking, and/or augmenting. In total, nine independent experimental studies were included (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in a final sample of nine journal articles, describing 14 experimental studies. However, after reading these papers, both reviewers discarded five studies (i.e., Gaschler, Marewski, Wenke, & Frensch, 2014; Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986; McAuliffe, Hughes, & Barnes-Holmes, 2014, Experiment 1; Ninness, Ninness, Sherman, & Schotta, 1998) because they did not state in the abstract or introduction that their aim was to investigate pliance, tracking, and/or augmenting. In total, nine independent experimental studies were included (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…During the last two decades, there has been a growing body of interest about selfassessment in the educational environment, especially because of evidence that it enhances student acquisition of some academic and social skills [1][2][3][4][5]14]. In addition, several studies revealed that self-assessment is a sine qua non for effective learning [2,6,15].…”
Section: Theoretical Framework 21 Self-assessmentmentioning
confidence: 99%
“…Feedback should be focused not only on strengths and weaknesses, but also on offering corrective advice, which leads students to higher order learning goals. In the research literature there are studies about this issue which compare self-assessment with and without feedback: Outcomes suggest that self-regulation with feedback helps students recognize mistakes and correct them because it directs them to a higher level of awareness and comprehension of failures [5,14].…”
Section: Theoretical Framework 21 Self-assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed studies show that the "reliability and validity of self-assessment tends to be higher in relation to the ability of the learner, the amount of scaffolding, practice and feedback and the degree of advancement in the course, rather than chronological age" (Topping 2003, p. 65). There are also some other factors which researchers (eg, Fontana and Fernandes 1994;Ninness et al 1998;Ward et al 2002) consider to be effective in reliability and validity of self-assessment. In Topping (2003, p. 65) words these factors include "the nature of the subject area, the nature of the product or performance assessed, the nature and clarity of the assessment criteria, the nature of assessment instrumentation, and cultural and gender differences.…”
Section: Issues In Implementing Self-assessmentmentioning
confidence: 99%